Design and technological solutions in development of highly efficent processing technology pressure - A. V. Evstifeev; A. A. Alexandrov; V. V. Evstifeev (Вестник СибАДИ, 2017)
On the basis of long-term experience of introduction of processes of volume and sheet stamping comparative features of development of technologies and the form-building tool, and, including, the providing shaped details with the application of the smaller deforming forces are presented when saving of the set characteristics of durability and plasticity, and also economy of materials. Rational technological process can be created only in the careful analysis of a set of known and original ways of forming of preparations and control of structure of metal and a form of a forging.